PENGARUH MANAJEMEN STRES TERHADAP PENURUNAN KADAR GULA DARAH PADA PENDERITA DIABETES MELLITUS DI DESA CINTA RAKYAT KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG TAHUN 2020 - Edisyah Putra Ritonga; Rizky Wahyu Ningsih (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2021)
Milletus diabetes is an emergency in a condition that is concerned with increased blood and specific specific symptoms, namely urine that tastes sweet and in large quantities. Stress is the body's response that is not specific to every need that is not disturbed, a universal phenomenon that occurs in everyday life and cannot be avoided, every person who experiences it, stress has a total impact on the individual, namely physical, psychological, intellectual, social and spiritually, stress can threaten the physiological balance. The type of research used in this research is quantitative by using a quasi experimental research design with the type of One Group Pretest-Posttest Design. The population in this study were residents of hamlet IX and hamlet X in Cinta Rakyat village, the total population in this study were 30 people with Diabetes Milletus disease. The sample size of this study is the entire population according to the criteria set in 30 people with Diabetes Milletus. Univariate and bivariate data analysis using the Wilcoxon Test. a significant value of 0.002 which means that it indicates acceptance and value (α = 0.005) = 0.002 <0.005. It is expected that residents and also respondents in IX and X Dusun Cinta Rakyat Village must be able to carry out non-pharmacological stress management therapy at home so that diabetes mellitus can be prevented.